Palmatine Attenuates Metastatic Lung Colonization of Triple Negative Breast Cancer Cells - Selase Ativui; Cynthia A. Danquah; Paul Poku Sampene Ossei; Michael Ofori (Frontiers Media S.A., 2022)
Background: Metastatic breast cancer to the lungs is a serious, life-threatening complication that is difficult to cure. Circulating tumor cells play a key role in the metastatic spread of breast cancer to the lungs via the lymphatic or circulatory system. Palmatine is a protoberberine alkaloid, identified as an active component of traditional African herbal preparations. Palmatine has antimetastatic and antiproliferative effects. The inhibitory activity of palmatine on the metastatic colonization of triple negative breast cancer cells in the lungs was investigated in this study.Methods: 4T1 triple breast cancer cells were transplanted synergically to the thoracic duct of the female balb/c mice via the lymphatic system. Palmatine 1, 5 and 10 mg/kg were administered for 28 days. The lungs were analyzed for levels of arterial blood gas, histological damage, immunohistochemical expression of the metastasis-associated protein 1 (MTA1) and tumor suppressor p53 (p53).Results: Administering palmatine 1-10 mg/kg dose dependently improved hypoxemia, ameliorated metastasis associated lung injury; histology score of 3.33 ± 0.33, 1.67 ± 0.33, 1.33 ± 0.33, decreased lung MTA1 (2.19 ± 0.12, 1.83 ± 0.04, 1.84 ± 0.05) and increased p53 expression (1.99 ± 0.06, 2.27 ± 0.12, 2.34 ± 0.12) respectively.Conclusion: Palmatine preserved lung morphology and demonstrated therapeutic potential in aiding the treatment of lung metastasis.